Pengaruh Penyuluhan Tentang Stunting Terhadap Pengetahuan dan Sikap Ibu yang Memiliki Balita di Posyandu Melati Desa Lambur 2 - Yuristina, Amanda (Universitas Batanghari Jambi, 2024)
Stunting in children is a chronic nutritional problem due to inadequate nutritional intake in the long term combined with infectious diseases in children and environmental problems. Stunting needs special attention because it can increase the risk of death in children, and hinder children's physical and mental development. Lack of nutritional knowledge or lack of applying nutritional knowledge in daily life can cause nutritional problems. Malnourishment in children can be caused by the attitude or behavior of parents, especially mothers who are a factor in choosing food that is not correct, choosing food ingredients, the availability of sufficient quantities of food and the variety of types of food is influenced by the level of knowledge of mothers about food and nutrition. Mother's attitude is greatly influenced by her knowledge.This study used a one group pretest-posttest design in October 2022 at Posyandu Melati, Lambur Village 2. The total population was 187 respondents with a sample using simple sampling 30 respondents. Data analysis used the t test. The results of this study found that there was an effect of counseling about stunting on the knowledge (p-value 0.008) and attitude (p-value 0.000) of mothers who had toddlers at Posyandu Melati Lambur 2 Village.The conclusion obtained in this study is that there is an influence of counseling about stunting on the knowledge and attitudes of mothers who have toddlers at Posyandu Melati, Lambur 2 Village.